Immune-Enhancing Nutrition in Surgical and Critical Care - Pollock, Graham R. Y. (Mo Med, 2012)
Immune-enhancing nutrition, or “immunonutrition,” refers to the use of specialized nutrients, including glutamine, alanine, omega-3 fatty acids, and others, that help regulate the body’s response to illness and injury. Clinical studies have demonstrated some very specific benefits, including fewer infectious complications and shorter length of hospitalization, in certain populations including high-risk surgical patients, trauma victims, and the critically-ill. Nationally recognized guidelines support the use of immune-enhancing nutrition in high-risk patients.